In-vitro inhibitory effect of ethanolic and methanolic extract of Scrophulari astriata on Candida spp. - Mandana Ahmadi; Hossein Mahdavi; Mahboobeh Madani; Zohreh Hadadi (Mazandaran University of Medical Sciences, 2016)
Candida species are the most common cause of opportunistic fungal infection worldwide. Due to increasing resistance of fungi against conventional drugs, as well as their side effects, alternative natural products have become a renewed interest. In the current study, the anti-Candida activities of Scrophularia striata extract were examined. In this experimental study, microdilution assay and well diffusion test  were used to determine invitro anti-fungal effects of ethanolic and methanolic extract of Scrophulari astriata on four species of Candida including Candida albicans ATCC 1167, ATCC 1677, tropicalis, and glabrata. The results showed that 100 mg/ml methanolic extract has more anticandida activity than ethanolic extract. Diameter of inhibiting growth environment for ethanol extract was 37 mm, and MIC and MFC were 2.1 and 41.5 mm/ml. Results show that ethanolic and methanolic extract of Scrophularia striata have anti-fungal activities. Therefore results of this study suggest this extract is a promising anti-fungal agent, and future experiments will interest for performing in vivo study.